Efficacy Comparison of Intravitreal Anti-VEGF Therapy for Three Subtypes of Neovascular Age-Related Macular Degeneration: A Systematic Review and Meta-Analysis - Jianqing Li; Jiayi Xu; Yiyi Chen; Jiaju Zhang; Yihong Cao; Peirong Lu (Journal of Ophthalmology)
Purpose. Intravitreal antivascular endothelial growth factor (anti-VEGF) therapy has been widely used for the treatment of neovascularization (NV) secondary to age-related macular degeneration (AMD). This study aimed to compare the efficacy among different subtypes of neovascular age-related macular degeneration (nAMD). Methods. PubMed, Embase, and the Cochrane Library were searched for eligible studies. We performed meta-analysis using Review Manager 5.3 and Stata/SE 12.0. Results. A total of 24 studies met our inclusion criteria and were included in the systematic review. At 3 months, the mean logarithm of the minimum angle of resolution (logMAR) improvements were −0.09, −0.18, and −0.23 for type 1, 2, and 3, respectively, while the mean macular thickness (MT) changes were −104.83, −130.76, and −196.29 μm. At 12 months, the mean changes in Early Treatment of Diabetic Retinopathy Study (ETDRS) letters were 6.38, 8.12, and 9.37, while the MT decrease was 126.51, 126.52, and 139.85 μm, respectively. However, statistically significant difference was only found between type 1 and 3 in vision improvement, both in the short term (p=0.0002) and long term (p=0.01). Conclusions. The reactivity to VEGF inhibitors varied among different subtypes of nAMD. The efficacy of intravitreal anti-VEGF therapy in type 3 nAMD was statistically better than type 1 when considering vision improvement at 3 and 12 months. Thus, the lesion subtype is a predictor for the treatment outcome which can help guide prognosis.